2013
DOI: 10.1103/physrevd.88.033018
|View full text |Cite
|
Sign up to set email alerts
|

Quark and leptonic mixing patterns from the breakdown of a common discrete flavor symmetry

Abstract: Assuming the Majorana nature of neutrinos, we recently performed a scan of leptonic mixing patterns derived from finite discrete groups of order less than 1536. Here we show that the 3 groups identified there as giving predictions close to experiment also contain another class of Abelian subgroups that predict an interesting leading-order quark mixing pattern where only the Cabibbo angle is generated at leading order. We further broaden our study by assuming that neutrinos are Dirac particles and find 4 groups… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(97 citation statements)
references
References 31 publications
4
93
0
Order By: Relevance
“…5 We find that the two smaller groups Σ(36×3) and Σ(72×3) only give rise to a few new mixing patterns, while the larger groups lead to several new patterns, since they have a richer structure of subgroups. Generically one sees (as already suggested by the scans of groups making use of the computer program GAP [12,13,15]) that only very few patterns are well-compatible with the experimental data of all three different mixing angles [3], if only small corrections are admitted, i.e. for each group one to two.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…5 We find that the two smaller groups Σ(36×3) and Σ(72×3) only give rise to a few new mixing patterns, while the larger groups lead to several new patterns, since they have a richer structure of subgroups. Generically one sees (as already suggested by the scans of groups making use of the computer program GAP [12,13,15]) that only very few patterns are well-compatible with the experimental data of all three different mixing angles [3], if only small corrections are admitted, i.e. for each group one to two.…”
Section: Introductionmentioning
confidence: 70%
“…3 The group Σ(36) is among the finite groups which can appear as symmetry group of the scalar sector of a three Higgs doublet model without leading to a potential with a continuous symmetry [21]. 4 This is in contrast to the recently performed scans of groups with an order smaller than 200 [15], an order smaller than 512 [12] or an order smaller than 1536 [13] that had the scope to only figure Among these four groups only Σ(360 × 3) has Klein subgroups and is thus suitable as G l , if neutrinos are assumed to be Majorana particles. Σ(36 × 3), Σ(72 × 3) and Σ(216 × 3) instead are only appropriate as G l , if neutrinos are Dirac particles or only one of the Z 2 symmetries of the neutrino mass matrix is contained in G l .…”
Section: Introductionmentioning
confidence: 97%
“…In several of these models quarks are included via SU(5) unification, but typically vacuum alignment does not determine the quark mixing angles. However, in a purely symmetry approach, the direct approach has been extended to the quark sector, where a subgroup of the discrete family symmetry is used to constrain also the quark mixing angles, in analogy with the procedure followed for the Klein symmetry in the neutrino sector [21][22][23], but no realistic model has been proposed. In some such approaches [22,23], the symmetry groups can be quite large, for example ∆(6n 2 ) for large values of n [24].…”
Section: Su(4)mentioning
confidence: 99%
“…In such models, it has been shown that the vacuum alignment completely breaks the A 4 symmetry, and such models are therefore referred to as "indirect" models [26]. Such "indirect" models are highly predictive and do not require such large discrete groups as the "direct" models where the Klein symmetry of the neutrino mass matrix is identified as a subgroup of the family symmetry [27][28][29].…”
Section: Jhep08(2014)130mentioning
confidence: 99%